Self-assembly superstructure ferrite-dielectric ceramic composite substrate and preparation method thereof
Through the preparation method of self-assembled superstructure ferrite-dipulated ceramic composite substrate, the problems existing in the preparation process of Y-type ferrite applications and composite substrates are solved, and the effects of high-intensity, low-magnetic field requirements and wide spectrum applications are achieved.
Patent Information
- Application Number
- CN202411641391.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-18
AI Technical Summary
At this stage, in order to realize the application of Y-type ferrite, a stable magnetic field of more than 10,000 Oe is required. In addition, the existing composite substrates have problems such as sealing stress cracking and incomplete solder filling during the preparation process, resulting in high production costs and limited component integration.
The self-assembled superstructure ferrite-dipulated ceramic composite substrate is adopted to screen ferrite powders and dielectric ceramic powders with magnetic permeability meet the requirements, dispersed in water containing water-soluble binder and crosslinker to form ceramic slurry, and the applied magnetic field direction and strength are controlled in the casting machine, casting and drying are carried out, forming a laminated casting sheet and sintering, obtaining a dense composite substrate.
It improves the mechanical strength and microscopic order of the composite substrate, reduces the required applied magnetic field strength, improves the ferrite powder content and the mechanical properties of the substrate, reduces production costs, and realizes wide spectrum application.
Smart Images

Figure CN119735433A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-performance substrate preparation for the electronics industry, and in particular relates to a self-assembled superstructure ferrite-dielectric ceramic composite substrate and a preparation method thereof. Background Art
[0002] Ferrite-dielectric ceramic composite substrate is a new generation of microwave ceramic substrate. Ferrite can realize the signal separation, filtering, transceiver and other functions of electronic components, which can effectively improve the working spectrum width and working power of communication equipment, and is conducive to the realization of millimeter wave communication. Therefore, it is widely used in 5G communication, wireless monitoring, artificial intelligence and other fields. 12 O 22 ) Hexagonal ferrite materials have great application prospects in the millimeter wave field due to their extremely high magnetocrystalline anisotropy and the characteristics of the easy magnetization plane in the vertical direction. However, at present, in order to realize Y-type ferrite, a steady magnetic field with a magnetic field strength of more than 10,000Oe is often required. Since the conditions for generating a steady magnetic field of this intensity are extremely harsh, it is difficult for the equipment to achieve wide spectrum applications.
[0003] On the other hand, the more advanced composite substrate currently uses a method of nesting a dielectric ceramic substrate and sealing ferrite to prepare an integrated substrate. However, this type of composite substrate often has serious problems such as sealing stress cracking, inadequate solder filling in the sealing area, and breakage during processing, resulting in high production costs and limited component integration. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate which can improve the strength of the composite substrate and reduce the required external magnetic field strength.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate comprises the following steps:
[0007] Step 1: Screening ferrite powder and dielectric ceramic powder whose magnetic conductivity meets the requirements, wherein the saturation magnetization intensity of the ferrite powder is greater than the saturation magnetization intensity of the dielectric ceramic powder;
[0008] Step 2: dispersing ferrite powder and dielectric ceramic powder in water containing a water-soluble binder and a cross-linking agent to obtain a ceramic slurry;
[0009] Step 3, injecting the ceramic slurry into the material tank of the tape casting machine, and controlling the direction and intensity of the external magnetic field according to the microscopic sequence requirements; the angle between the magnetic field direction and the tape casting direction of the ceramic slurry is a first preset angle;
[0010] Step 4: The ceramic slurry flows out of the material tank onto the casting bed of the casting machine for casting. During the casting process, the ceramic slurry is dried to remove excess water from the ceramic slurry. The magnetic field strength is kept constant during the drying process. After drying, a self-assembled single-layer composite ceramic substrate of a certain thickness is obtained.
[0011] Step 5, cutting the single-layer composite ceramic substrate and stacking them together, and performing vacuuming and warm isostatic pressing to obtain a laminated cast sheet;
[0012] Step 6: Cut the laminated cast sheet into ceramic blanks of certain specifications and sizes. After drying, debinding and sintering, the ceramic blanks are obtained to obtain a dense ferrite-dielectric ceramic composite substrate.
[0013] The saturation magnetization intensity of the ferrite powder is 8000-13000 Oe, and the specific surface area of the ferrite powder is 10-15 g / m 2 , the particle size D of the ferrite powder 50 :0.05~0.5μm;
[0014] The specific surface area of the dielectric ceramic powder is 10 to 15 g / m 2 , the particle size D of the dielectric ceramic powder 50 :0.05~0.5μm;
[0015] The saturation magnetization intensity of the ferrite powder is 9000 to 12000 Oe; the particle size D of the ferrite powder is 50 :0.1~0.3μm;
[0016] The particle size D of the dielectric ceramic powder 50 0.1~0.3μm.
[0017] The solid content of the ceramic slurry is 50-54 Vol%;
[0018] The viscosity of the ceramic slurry is 100 to 500 mPa·s;
[0019] The water-soluble binder is a water-based gel medium that is volatile and can help disperse the dielectric ceramic powder;
[0020] The cross-linking agent is ethylenediamine, diethylenetriamine or dipropylenetriamine.
[0021] The viscosity of the ceramic slurry is 100-200 mPa·s;
[0022] The binder is polyvinyl alcohol, acrylic acid-polyacrylic acid amine or acrylamide;
[0023] The mass ratio of the ferrite powder, dielectric ceramic powder, cross-linking agent and adhesive is (25-30):(25-30):1:(0.5-1);
[0024] The volume ratio of the ferrite powder and the dielectric ceramic powder is the same.
[0025] The direction of the magnetic field can be adjusted in space according to demand, and the first preset angle is 0-90°; the magnetic field strength is between 5,000 and 15,000 GS, and the saturation magnetization strength provided is 5,000 to 15,000 Oe.
[0026] The magnetic field strength is between 6,500 and 13,000 GS, and the saturation magnetization provided is between 6,500 and 13,000 Oe.
[0027] The thickness of the single-layer composite ceramic substrate is 15 to 20 μm;
[0028] The thickness of the laminated cast sheet is 0.8 to 1 mm;
[0029] The drying temperature on the casting bed is 60°C to 80°C, and the drying time is 5 to 15 minutes;
[0030] The drying is carried out in a blast oven at 60°C to 80°C for 8 to 12 hours;
[0031] The ceramic batch is a square substrate with a length and width of 1 to 2 inches, and a thickness of the square substrate is 0.8 to 1 mm.
[0032] The temperature rise curve during the debinding process is:
[0033]
[0034] RT is the room temperature during debinding; T1 is the water removal temperature; T2-T4 are the residual organic solvent ablation temperatures; T5 is the debinding temperature;
[0035] Among them, T1 is 150℃~200℃, T2 is 250℃~350℃, T3 is 400℃~450℃, T4 is 500℃~650℃, and T5 is 700℃~900℃;
[0036] The sintering temperature curve is:
[0037]
[0038] Among them, RT is the room temperature during sintering; T6 is the relatively low temperature section temperature; T7 is the high temperature sintering temperature; T6 is 150℃~200℃, T7 is 1200℃~1600℃, and the load during sintering is 0.04g / mm 2 .
[0039] The invention also provides a self-assembled superstructure ferrite-dielectric ceramic composite substrate, which is prepared according to the preparation method.
[0040] By means of the above technical solution, the present invention has at least the following advantages:
[0041] 1. The microscopic orderliness of the ferrite-dielectric ceramic composite substrate prepared by the present invention greatly improves the mechanical strength. According to the test of GB / T 6569-2006 Fine Ceramics Bending Strength Test Method, the bending strength of the composite ceramic is increased from 200MPa to about 350MPa.
[0042] 2. The present invention controls the orientation direction of the magnetic field during self-assembly. By controlling the direction and intensity of the magnetic field, the magnetic field direction can be in different directions such as 90°, 30° or 45°, thereby controlling the orientation of the ferrite powder part, reducing the saturation magnetic induction intensity of the ferrite powder, and making the external magnetic field required for the self-assembled composite substrate lower during operation; the microscopic orderliness of the prepared ferrite-dielectric ceramic composite substrate greatly reduces the external magnetic field intensity required during operation. According to tests, the magnetic field intensity required for the composite ceramic substrate to work is reduced by 10% to 30%.
[0043] 3. The tape casting lamination method can effectively increase the ferrite powder content of the composite substrate. After testing, the ferrite powder content is increased from 35% of the general nested structure to 50%. At the same time, the present invention can achieve the purpose of controlling the assembly ratio of the self-assembled composite substrate by controlling the solid content in the ceramic slurry, increasing the proportion of ferrite powder in the ferrite-dielectric ceramic, that is, the assembly ratio, which can improve the mechanical properties of the self-assembled composite substrate and is not easy to crack during the processing process.
[0044] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a structural schematic diagram of a ferrite-dielectric ceramic composite substrate provided by an embodiment of the present invention;
[0046] Figure 2 It is another structural schematic diagram of the ferrite-dielectric ceramic composite substrate provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0047] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0048] like Figure 1 and Figure 2 As shown in the figure, a new generation of composite ceramic substrates using self-assembled metamaterials is used. An external magnetic field is pre-applied to the Y-type ferrite using a magnetic field induction method. Since the magnetic crystal planes of the Y-type ferrite will be oriented under the external magnetic field, and due to the different saturation magnetization intensities of the Y-type ferrite and the dielectric ceramic powder, and the anisotropy of the magnetic crystal planes of the ferrite, orientation is generated, and finally the following is formed: Figure 1 and Figure 2 The microstructure ordered and controllable ferrite-dielectric ceramic composite substrate shown. The "sandwich" structure formed by ferrite 1 and dielectric ceramic 2 avoids the stress cracking problem in the nested sealing process, and provides a ferrite microstructure with magnetic crystal plane orientation, which significantly reduces the working magnetic field intensity required for ferrite and significantly increases the ferrite content, and ultimately realizes the miniaturization of electronic components.
[0049] The present invention will be further described below by means of specific embodiments:
[0050] Example 1
[0051] A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate comprises the following steps:
[0052] Step 1: Screen out the saturation magnetization of 12000Oe and the specific surface area of 15g / m 2 , particle size D 50 The ferrite powder is 0.2μm and the specific surface area is 15g / m 2 , particle size D 50 0.2μm dielectric ceramic powder;
[0053] Step 2: Disperse ferrite powder and dielectric ceramic powder in water containing a water-soluble binder and a cross-linking agent, wherein the mass ratio of ferrite powder: dielectric ceramic powder: binder: cross-linking agent is 25:25:1:1; obtain a ceramic slurry with a viscosity of 150 mPa·s and a solid content of 50 Vol% of the ceramic slurry;
[0054] The binder is polyvinyl alcohol;
[0055] The cross-linking agent is ethylenediamine;
[0056] Step 3, injecting the ceramic slurry into the trough of the tape casting machine, and controlling the direction and intensity of the external magnetic field according to the microscopic sequence requirements;
[0057] Control the direction and strength of the applied magnetic field according to the microscopic sequence requirements, including: if the applied magnetic field strength is insufficient or the working space is limited, the magnetic field strength should be increased in the 90° direction during the molding process to ensure that the working window of the produced cast film is the widest;
[0058] When the strength of the applied magnetic field is sufficient but a narrow working window is required, the magnetic field strength should be reduced so that the produced cast sheet meets the working window requirements. The magnetic field strength and direction can be modified as long as there is a certain order to ensure that it can work in a narrow frequency under a limited space and a limited applied magnetic field. The magnetic field direction is a direction that forms a certain angle with the casting direction of the ceramic slurry; preferably, it forms a 90° angle with the casting bed.
[0059] In this embodiment, an N-pole magnet is placed 0.5m above the casting bed, and an S-pole magnet is placed 0.5m below the casting bed. The line connecting the centers of the two magnets is perpendicular to the casting direction, that is, the angle between the line connecting the centers of the two magnets and the casting direction is 90°, that is, the direction of the magnetic field is 90° to the casting direction of the ceramic slurry; the magnetic field strength provided by the two magnets is 12000GS, and the saturation magnetization intensity provided is 12000Oe.
[0060] Step 4, the ceramic slurry flows out of the material tank onto the casting bed of the casting machine for casting. During the casting process, the ceramic slurry is dried at 60°C for 10 minutes to remove excess water from the ceramic slurry. The magnetic field strength is kept constant at 8500GS during the drying process. During this process, the adhesive volatilizes and the self-assembled ferrite-dielectric ceramic ordered sequence is self-assembled. After drying, a self-assembled single-layer composite ceramic substrate with a thickness of 18 μm is obtained; the thickness of the single-layer composite ceramic substrate is controlled by controlling the scraper height and / or the viscosity of the ceramic slurry;
[0061] Step 5: Cut the single-layer composite ceramic substrate into single-layer cast sheets with a length and width of 1 inch in the cutting area of the casting bed, stack multiple single-layer cast sheets together, and perform vacuuming and warm isostatic pressing to obtain a laminated cast sheet with a thickness of 0.9 mm;
[0062] Step 6: drying the laminated cast sheet in a blast oven at 60° C. for 12 hours, debinding and sintering to obtain a dense ferrite-dielectric ceramic composite substrate;
[0063] The maximum temperature of the debinding process does not exceed 900°C, and the temperature rise curve during the debinding process is:
[0064]
[0065] RT is the room temperature during debinding; T1 is the water removal temperature; T2-T4 are the residual organic solvent ablation temperatures; T5 is the debinding temperature;
[0066] Among them, T1 is 180℃, T2 is 330℃, T3 is 400℃, T4 is 550℃, and T5 is 800℃;
[0067] The sintering temperature curve is:
[0068]
[0069] Among them, RT is the room temperature during sintering; T6 is the relatively low temperature section temperature; T7 is the high temperature sintering temperature; T6 is 200℃, T7 is 1400℃, and the load during sintering is 0.04g / mm 2 .
[0070] Example 2
[0071] A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate comprises the following steps:
[0072] Step 1: Screen out the saturation magnetization of 9000Oe and the specific surface area of 10g / m 2 , particle size D 50 The ferrite powder has a diameter of 0.3 μm and a specific surface area of 12 g / m 2 , particle size D 50 0.1μm dielectric ceramic powder;
[0073] Step 2: Disperse ferrite powder and dielectric ceramic powder in water containing a water-soluble binder and a cross-linking agent, wherein the mass ratio of ferrite powder: dielectric ceramic powder: binder: cross-linking agent is 25:25:1:0.5, and obtain a ceramic slurry with a viscosity of 200 mPa·s and a solid content of 52 Vol% of the ceramic slurry;
[0074] The water-soluble binder is acrylic acid-polyacrylamide;
[0075] The cross-linking agent is diethylenetriamine;
[0076] Step 3, injecting the ceramic slurry into the material tank of the tape casting machine, and controlling the direction and intensity of the external magnetic field according to the microscopic sequence requirements;
[0077] An N-pole magnet is placed directly above the casting bed, and an S-pole magnet is placed directly below the casting bed. The angle between the center of the two magnets and the casting direction is 85°. The magnetic field strength provided by the two magnets is 6500GS, and the saturation magnetization intensity provided is 6500Oe.
[0078] Step 4: The ceramic slurry flows out of the material tank onto the casting bed of the casting machine for casting. During the casting process, the ceramic slurry is dried at 70°C for 15 minutes to remove excess water from the ceramic slurry. The magnetic field strength is kept constant at 6500GS during the drying process. During this process, the adhesive evaporates and the self-assembled ferrite-dielectric ceramic ordered sequence is self-assembled. After drying, a self-assembled single-layer composite ceramic substrate with a thickness of 20 μm is obtained.
[0079] Step 5: Cut the single-layer composite ceramic substrate into single-layer cast sheets with a length and width of 2 inches in the cutting area of the casting bed, stack multiple single-layer cast sheets together, and obtain a laminated cast sheet with a thickness of 0.8 mm after vacuuming and warm isostatic pressing;
[0080] Step 6: drying the laminated cast sheet in a blast oven at 70° C. for 10 hours, debinding, and sintering to obtain a dense ferrite-dielectric ceramic composite substrate;
[0081] The maximum temperature of the debinding process does not exceed 900°C, and the temperature rise curve during the debinding process is:
[0082]
[0083] RT is the room temperature during debinding; T1 is the water removal temperature; T2-T4 are the residual organic solvent ablation temperatures; T5 is the debinding temperature;
[0084] Among them, T1 is 200℃, T2 is 350℃, T3 is 450℃, T4 is 650℃, and T5 is 900℃;
[0085] The sintering temperature curve is:
[0086]
[0087] Among them, RT is the room temperature during sintering; T6 is the relatively low temperature section temperature; T7 is the high temperature sintering temperature; T6 is 180℃, T7 is 1200℃, and the load during sintering is 0.04g / mm 2 .
[0088] Example 3
[0089] A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate comprises the following steps:
[0090] Step 1: Screen out the magnetic saturation intensity of 10000Oe and the specific surface area of 13g / m 2 , particle size D 50 The ferrite powder is 0.1μm and the specific surface area is 10g / m 2 , particle size D 50 0.5μm dielectric ceramic powder;
[0091] Step 2: Disperse ferrite and dielectric ceramic powder in water containing a water-soluble binder and a cross-linking agent to prepare a ceramic slurry with a solid content of 54 Vol% and a viscosity of 500 mPa·s, wherein the mass ratio of ferrite: dielectric ceramic powder: cross-linking agent: binder is 30:30:1:1;
[0092] The water-soluble binder is acrylamide;
[0093] The cross-linking agent is dipropylene triamine;
[0094] Step 3, injecting the ceramic slurry into the trough of the tape casting machine, and controlling the direction and intensity of the external magnetic field according to the microscopic sequence requirements;
[0095] During the casting process, an N-pole magnet is placed at a horizontal height of 0.5m above the casting bed, and an S-pole magnet is placed at a horizontal height of 0.5m below the casting bed. The angle between the center of the two magnets and the casting direction is 45°. The magnetic field strength provided by the two magnets is 10000GS, and the saturation magnetization intensity provided is 10000Oe.
[0096] Step 4: The ceramic slurry flows out of the material tank onto the casting bed of the casting machine for casting. During the casting process, the ceramic slurry is dried at 80°C for 5 minutes to remove excess water from the ceramic slurry. The magnetic field strength is kept constant at 10000GS during the drying process. During this process, the adhesive evaporates and the self-assembled ferrite-dielectric ceramic ordered sequence is self-assembled. After drying, a self-assembled single-layer composite ceramic substrate with a thickness of 15 μm is obtained.
[0097] Step 5: Cut the single-layer composite ceramic substrate into single-layer cast sheets with a length and width of 1.5 inches in the cutting area of the casting bed, stack multiple single-layer cast sheets together, and obtain a laminated cast sheet with a thickness of 1.0 mm after vacuuming and warm isostatic pressing;
[0098] Step 6: drying the laminated cast sheet in a blast oven at 80° C. for 8 h, debinding, and sintering to obtain a dense ferrite-dielectric ceramic composite substrate;
[0099] The maximum temperature of the debinding process does not exceed 900°C, and the temperature rise curve during the debinding process is:
[0100]
[0101]
[0102] RT is the room temperature during debinding; T1 is the water removal temperature; T2-T4 are the residual organic solvent ablation temperatures; T5 is the debinding temperature;
[0103] Among them, T1 is 150℃, T2 is 250℃, T3 is 400℃, T4 is 500℃, and T5 is 700℃;
[0104] The sintering temperature curve is:
[0105]
[0106] Among them, RT is the room temperature during sintering; T6 is the relatively low temperature section temperature; T7 is the high temperature sintering temperature; T6 is 150℃, T7 is 1600℃, and the load during sintering is 0.04g / mm 2 .
[0107] Example 4
[0108] A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate is substantially the same as that in Example 1, except that:
[0109] In step 1: the magnetic saturation intensity of ferrite is 13000Oe, and the particle size of ferrite is D 50 :0.05μm; particle size D of dielectric ceramic powder 50 :0.3μm.
[0110] In step 2: the mass ratio of ferrite: dielectric ceramic powder: cross-linking agent: adhesive is 28:28:1:0.8.
[0111] In step 3: the magnetic field strength provided by the two magnets is 15000 GS, and the saturation magnetization strength provided is 15000 Oe.
[0112] Example 5
[0113] A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate is substantially the same as that in Example 1, except that:
[0114] In step 1: the magnetic saturation intensity of the ferrite is 8000Oe;
[0115] In step 2: the mass ratio of ferrite: dielectric ceramic powder: cross-linking agent: adhesive is 27:27:1:0.6.
[0116] In step 3: the magnetic field strength provided by the two magnets is 5000 GS, the saturation magnetization provided is 5000 Oe, and the angle between the line connecting the centers of the two magnets and the casting direction is 90°.
[0117] Table 1 Performance comparison between each embodiment and existing magnesium titanate ceramic substrate
[0118]
[0119] It can be seen from Table 1 above that the magnetic field strength required for the present invention to work is less than the magnetic field strength required for the existing ceramic substrate to work. The external magnetic field in Example 5 during the casting process is relatively small, resulting in the phenomenon of inadequate orientation during the directional arrangement, and the orientation is not complete or the optimal orientation is not achieved. Therefore, the ferrite-dielectric ceramic composite substrate prepared in Example 5 requires a higher magnetic field strength when working, and the magnetic field strength required for its work is 11000GS. The present invention controls the arrangement orientation and stratification of the dielectric ceramic powder and the ferrite powder during the casting process by controlling the strength and direction of the external magnetic field, thereby achieving control of the stratification of ferrite and dielectric ceramic and the orientation of the magnetic surface of ferrite. The closer the magnetic field strength applied in the vertical direction of the casting is to or exceeds the saturation magnetization of the ferrite powder, the more obvious the directional arrangement of the ferrite, and the smaller the external magnetic field required for the ferrite-dielectric ceramic composite substrate after sintering when working. The magnetic field strength required for the existing ceramic substrate to work is not lower than the saturation magnetization of the ferrite powder, while the magnetic field strength required for the work by the preparation method of the present invention is lower than the saturation magnetization of the ferrite powder. The present invention achieves the purpose of reducing the size of electronic components and improving the strength of the composite substrate through densification sintering. Further controlling the working magnetic field strength can widen the spectrum width, enabling the composite substrate to achieve wide spectrum application, and ultimately achieving the purpose of improving the mechanical strength, ferrite ratio and integration of the composite substrate, and reducing the strength of the external working magnetic field of the composite substrate.
[0120] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a self-assembled superstructure ferrite-dielectric ceramic composite substrate, characterized in that: The following steps are involved: Step 1: Screening ferrite powder and dielectric ceramic powder whose magnetic conductivity meets the requirements, wherein the saturation magnetization intensity of the ferrite powder is greater than the saturation magnetization intensity of the dielectric ceramic powder; Step 2: dispersing ferrite powder and dielectric ceramic powder in water containing a water-soluble binder and a cross-linking agent to obtain a ceramic slurry; Step 3, injecting the ceramic slurry into the material tank of the tape casting machine, and controlling the direction and intensity of the external magnetic field according to the microscopic sequence requirements; the angle between the magnetic field direction and the tape casting direction of the ceramic slurry is a first preset angle; Step 4: The ceramic slurry flows out of the material tank onto the casting bed of the casting machine for casting. During the casting process, the ceramic slurry is dried to remove excess water from the ceramic slurry. The magnetic field strength is kept constant during the drying process. After drying, a self-assembled single-layer composite ceramic substrate of a certain thickness is obtained. Step 5, cutting the single-layer composite ceramic substrate and stacking them together, and performing vacuuming and warm isostatic pressing to obtain a laminated cast sheet; Step 6: Cut the laminated cast sheet into ceramic blanks of certain specifications and sizes. After drying, debinding and sintering, the ceramic blanks are obtained to obtain a dense ferrite-dielectric ceramic composite substrate.
2. The preparation method according to claim 1, characterized in that: The saturation magnetization intensity of the ferrite powder is 8000-13000 Oe, and the specific surface area of the ferrite powder is 10-15 g / m 2 , the particle size D of the ferrite powder 50 :0.05~0.5μm; The specific surface area of the dielectric ceramic powder is 10 to 15 g / m 2 , the particle size D of the dielectric ceramic powder 50 :0.05~0.5μm.
3. The preparation method according to claim 2, characterized in that: The saturation magnetization intensity of the ferrite powder is 9000 to 12000 Oe; the particle size D of the ferrite powder is 50 :0.1~0.3μm; The particle size D of the dielectric ceramic powder 50 0.1~0.3μm.
4. The preparation method according to claim 1, characterized in that: The solid content of the ceramic slurry is 50-54 Vol%; The viscosity of the ceramic slurry is 100 to 500 mPa·s; The water-soluble binder is a water-based gel medium that is volatile and can help disperse the dielectric ceramic powder; The cross-linking agent is ethylenediamine, diethylenetriamine or dipropylenetriamine.
5. The preparation method according to claim 4, characterized in that: The viscosity of the ceramic slurry is 100-200 mPa·s; The binder is polyvinyl alcohol, acrylic acid-polyacrylic acid amine or acrylamide; The mass ratio of the ferrite powder, dielectric ceramic powder, cross-linking agent and adhesive is (25-30):(25-30):1:(0.5-1); The volume ratio of the ferrite powder and the dielectric ceramic powder is the same.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The direction of the magnetic field can be adjusted in space according to demand, and the first preset angle is 0-90°; the magnetic field strength is between 5,000 and 15,000 GS, and the saturation magnetization strength provided is 5,000 to 15,000 Oe.
7. The preparation method according to claim 6, characterized in that: The magnetic field strength is between 6,500 and 13,000 GS, and the saturation magnetization provided is between 6,500 and 13,000 Oe.
8. The preparation method according to claim 6, characterized in that: The thickness of the single-layer composite ceramic substrate is 15 to 20 μm; The thickness of the laminated cast sheet is 0.8 to 1 mm; The drying temperature on the casting bed is 60°C to 80°C, and the drying time is 5 to 15 minutes; The drying is carried out in a blast oven at 60°C to 80°C for 8 to 12 hours; The ceramic batch is a square substrate with a length and width of 1 to 2 inches, and a thickness of the square substrate is 0.8 to 1 mm.
9. The preparation method according to claim 6, characterized in that: The temperature rise curve during the debinding process is: RT is the room temperature during debinding; T1 is the water removal temperature; T2-T4 are the residual organic solvent ablation temperatures; T5 is the debinding temperature; Among them, T1 is 150℃~200℃, T2 is 250℃~350℃, T3 is 400℃~450℃, T4 is 500℃~650℃, and T5 is 700℃~900℃; The sintering temperature curve is: Among them, RT is the room temperature during sintering; T6 is the relatively low temperature section temperature; T7 is the high temperature sintering temperature; T6 is 150℃~200℃, T7 is 1200℃~1600℃, and the load during sintering is 0.04g / mm 2 .
10. A self-assembled superstructure ferrite-dielectric ceramic composite substrate, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of ferrite ceramic
CN103553585A
Ceramic dielectric-ferrite composite material and preparation method thereof
CN117024135A
Water-based tape casting slurry and method for preparing magnetoelectric composite ceramic sheet through water-based tape casting
CN117362025A